Learning Style and Achievement Learner Madrasah Ibtidaiyah - Tika, Firman (Cahaya Ilmu Cendekia Publisher, 2021)
Purpose of study: The purpose of this study is to determine the relationship between learning styles and learning outcomes. Methodology: This study used descriptive, correlational quantitative research. Researchers used a questionnaire to determine student learning styles. Learning outcomes obtained from students' final semester grades. Correlational learning styles and outcomes using spss. Main finding: Research findings indicate that learning styles do not show a correlation with learning outcomes. Novelty/Originality of this study: Learning outcomes are not determined by learning styles. One cannot judge a student by learning success is not determined by the student's learning style.